SPE Improved Oil Recovery Symposium 2012
DOI: 10.2118/153155-ms
|View full text |Cite
|
Sign up to set email alerts
|

Water Shutoff at Ultralow Temperatures Using Organically Crosslinked Polymer Gels

Abstract: Use of crosslinked polymer gels employing polymeric base materials and crosslinkers for shutting off water production in a variety of situations has been amply documented at formation temperatures ranging from ambient to > 400°F. However, there has not been much work reported on chemical systems that can provide adequate gel times and gel strengths at temperatures less than 80°F. The reaction rates and gel-strength-development rates are significantly lower at low temperatures, resulting in long gel time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…The gelation time is a function of salinity, polymer and cross-linker concentrations and temperature (Marfo et al 2015). (Reddy et al 2012) developed correlations for gelation time as a function of salinity for polyacrylamide polymer and polyamide crosslinker showing a linear relationship. The gelation time increases with an increase in salinity because the common ions decrease the nucleophilic capacity (Salehi et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The gelation time is a function of salinity, polymer and cross-linker concentrations and temperature (Marfo et al 2015). (Reddy et al 2012) developed correlations for gelation time as a function of salinity for polyacrylamide polymer and polyamide crosslinker showing a linear relationship. The gelation time increases with an increase in salinity because the common ions decrease the nucleophilic capacity (Salehi et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Produced water cost the petroleum industry about $45 billion in 2002 [5,6], and this could be on the increase with development of additional wells. High water cut comes with its associated problems such as corrosion, sand production, scale formation and loss of productivity [1,[7][8][9]. This occurrence is common with mature fields [10].…”
Section: Introductionmentioning
confidence: 99%
“…These equations showed that increasing the temperature shortened the gelation time of organically crosslinked gels. Reddy [9] developed correlations for gelation time as a function of degree of salinity of mixing fluid for KCl and NaCl. Their findings indicated a linear relation between gelation time and the salt concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these low temperature applications, gelant reaction and gelstrength-development rates are significantly lower compared to traditional encountered reservoir temperatures; this may yield long gelation times and weaker formed gels. Reddy et al (2012) discussed an HPAM/polyamine-crosslinker (organically crosslinked polymer-based) water shutoff gelant that may provide sufficient gelation times at temperatures lower than 80°F. Such gelants could be optimized with regards to gelation times development of rigid gels using activator chemicals and retarders as well as polymer/crosslinker ratios for the specific filed applications.…”
Section: Introductionmentioning
confidence: 99%